A SYSTEMATIC REVIEW OF THE RELATIONSHIP BETWEEN MIGRAINE AND SLEEP DISORDERS - Saidvaliyev, F.S. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Migraine and sleep disorders are prevalent chronic conditions that have a significant socioeconomic impact and can be burdensome. The exact nature of the relationship between these conditions and the underlying mechanisms is not completely understood. Recent research has identified central nervous system structures and neurotransmitters that play a role in both migraine and normal sleep architecture, indicating a possible causal role in the pathogenesis of both conditions. This systematic review aims to evaluate the existence of a causal relationship between migraine and sleep disorders, as well as to identify influencing factors. Identifying specific sleep disorders associated with migraine can help clinicians systematically assess their presence in migraine patients and implement combined treatment strategies.